Safety analysis of ex vivo‐expanded canine natural killer cells in a xenogeneic mouse model of graft‐versus‐host disease. Issue 2 (22nd April 2021) - Kim, Cheol‐Jung; Park, Se‐Cheol; Lee, Soo‐Hyeon; Lim, Yu‐Jin; Yoon, Meesun; Park, Jun‐Gyu; Baek, Yeong‐Bin; Cho, Kyoung‐Oh; Hong, Jeong Won; Shin, Dong‐Jun; Kim, Sang‐Ki
Abstract: Canine natural killer (NK) cells are large, granular lymphocytes that are neither B lymphocytes nor T lymphocytes. However, it has been reported that canine NK cells share some of the phenotypic characteristics of T lymphocytes, such as CD3 and CD5. Studies are needed to assess the safety of canine NK cells for immunotherapy, especially because the safety of using allogeneic NK cells as an immunotherapy for dogs has yet to be shown. In this study, the safety of cultured canine NK cells was assessed using a xenogeneic mouse model of graft‐versus‐host disease (GVHD). Mice were injected with either canine peripheral blood mononuclear cells (PBMCs) or cultured NK cells for 2 or 3 weeks. Data were then collected on changes in mice body weights, disease severity scores, and survival rates. Histopathological and immunohistochemical evaluations were also performed. All mice injected with canine PBMCs died within 45 days after injection. Severe clinical signs were caused by GVHD. The histopathological and immunohistochemical evaluations showed that mice injected with canine PBMCs had multiple lesions, including necrosis in their lungs, livers, kidneys, and stomachs, and the injected cells were present around the lesions. By contrast, no mice injected with cultured NK cells without removing the CD3 + TCR – cells exhibited any clinical abnormalities. Moreover, they all survived the 90‐day experimental period without exhibiting any histopathological changes. Accordingly, the results of this study suggest that canine NK cells do not cause significant side effects such as GVHD and allogeneic NK cells can safely be used for cancer immunotherapy in dogs. Graphical Abstract: Expanded canine NK cells do not cause GVHD in a xenogeneic GVHD model and can be investigated for cancer immunotherapy without removing the CD3 + TCR ‐ cells in dogs.